Limit theorems for solutions of multipoint boundary-value problems with a parameter in Sobolev spaces - Atlasiuk , O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.927We consider the most general class of multipoint boundary-value problems for systems of linear ordinary differential equations of an arbitrary order whose solutions belong to the given Sobolev space $W_p^{n+r},$ with $n≥ 0,$ $r≥ 1,$ and $1≤ p≤ ∞.$ We establish constructive sufficient conditions under which the solutions of these problems are continuous with respect to the parameter $ε$ at $ε=0$ in the space $W_p^{n+r}.$